Investigation of the First Hydrogenation of LaNi5 - Salma Sleiman; Samaneh Shahgaldi; Jacques Huot (Reactions)
The first hydrogenation of most metal hydrides is a lengthy process that usually requires high pressure and temperature. This, in turn, significantly increases the production cost of metal hydrides. In this paper, the low temperature hydride-forming LaNi5 was selected to investigate the mechanism of first hydrogenation. For the first time, the effect of particle size, temperature and pressure on the incubation time were studied. We found that the first hydrogenation of LaNi5 follows an Arrhenius process, with an activation energy of EA = 78 ± 4 kJ/mol H2. We also found that the pre-exponential factor depends on the applied pressure.